Phylotranscriptomics confirms Alveopora is sister to Montipora within the family Acroporidae - Richards, Zoe; Carvajal, J.I.; Wallace, C.C.; Wilson, N.G. (2019)
© 2019 The genus Alveopora is a scleractinian coral taxon whose phylogenetic classification has recently changed from the family Poritidae to Acroporidae. This change, which was made based on single-locus genetic data, has led to uncertainty about the placement of Alveopora and the ability for deep evolutionary relationships in these groups to be accurately recovered and represented by limited genetic datasets. We sought to characterize the higher-level position of Alveopora using newly available transcriptome data to confirm its placement within Acroporidae and resolve its closest ancestor. Here we present an analysis of a new 2031 gene dataset that confirms the placement of Alveopora within Acroporidae corroborating other single-locus (COI, 16S and ITS) analyses and a mitogenome dataset. We also resolve the position of Alveopora as sister to the genus Montipora. This has allowed the re-interpretation of morphology, and a rediagnosis of the family Acroporidae and the genus Alveopora.